An institutional framework for Bioinputs in Brazilian agriculture based on Ecological Economics - Souza, Fabiana Pereira de; Castilho, Tatiana Portela Ribeiro; Macedo, Luís Otávio Bau (Sustainability in Debate, 2022)
In search of sustainability, new patterns for production or consumption have been created in opposition to conventional products, such as biological inputs or "bioinputs". They are products, processes or technologies of animal, plant or microbial origin which can positively affect agricultural production. The adherence of rural producers to sustainable and economic agricultural practices, which use bioinputs, is growing in Brazil. They have been encouraged to adopt these products because of the existence of the National Bioinputs Program, created in 2020. The results show that several benefits have been associated with their use. However, inadequate handling can bring negative externalities that could be avoided. It requires an institutional framework to guide the country's production and use of bioinputs. This article proposes a new institutional framework based on ecological economics and institutionalism, considering Brazil's sociopolitical and environmental situation.